A Case of Hydropyometra Secondary to Vaginal Atresia: A Case Report - Mishra, Deepak; Sipai, Sani; Jha, Nitu Kumari; Ray, Pankaj (Medical Journal of Shree Birendra Hospital, 2022)
Hydrometrocolpos refers to the accumulation of secretions within the endometrial and endovaginal canal. The causes of retention of cervico-vaginal secretions are varied. Herein, we report a case of a seven-day-old female child presented to us for follow up as antenatal ultrasound done at nine months which had showed round cystic lesion with internal echoes in fetal lower abdomen. With the help of clinical examination and diagnostic imaging, the case was diagnosed as hydropyometra secondary to vaginal atresia and managed successfully by surgical intervention.